2021
DOI: 10.1111/jgs.17466
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and persistency of deficiency citations in Florida assisted living facilities

Abstract: Background: Assisted living facilities (ALFs) are plagued with quality issues but there are limited studies on the quality of ALFs. In Florida, state surveyors conduct inspections of ALFs and cite and/or fine facilities that are in violation of regulations. Yet, we do not know the types of quality problems identified and the extent to which facilities repeat such problems. In this study, we begin to fill this gap in our understanding of ALFs quality by summarizing the deficiency citations in Florida ALFs. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…Similar to past research on assisted living [4][5][6] and nursing homes 8 we found for-profit facilities had worse quality. Policymakers should question whether this ownership type is in the best interest of its residents.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to past research on assisted living [4][5][6] and nursing homes 8 we found for-profit facilities had worse quality. Policymakers should question whether this ownership type is in the best interest of its residents.…”
Section: Discussionsupporting
confidence: 88%
“…Due to the lack of federal regulation and wide variation in state regulation, 2,3 there is a lot unknown about the quality of care in this setting. Past research in Florida and Oregon find for‐profit, large and rural ALFs are cited more often 4–6 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation